Anaïs Nin : a sea of lies - Bischoff, Léonie (Fantagraphics Books, Inc., 2023)
"In lithe, sensuous colored pencils, this international prize-winning, impressionistic graphic biography traces the life, the affairs, and the artistic process of Anais Nin, one of the best-known authors of women's erotica in the 1920s and '30s"--